Selling out the city? Airbnb’s amateur and professional listings across cities, time, and hotspots Ausverkauf der Stadt? Amateur- und professionelle Airbnb-Angebote im Vergleich über Städte, Hotspots und die Zeit - Kirchner, Stefan; Pohl, Simon C. (Berliner Journal für Soziologie, 2024)
In the early days of its existence, Airbnb was heralded as a champion of the “sharing economy”, enabling amateur hosts to offer short-term lodging to a global community of guests. Since then, public debates and research have highlighted the rise of professional hosts as an indication for the commercialization of Airbnb. However, it is neither well understood how Airbnb listings developed across cities and time nor how they are distributed across local hotspots. The paper conceptualizes the Airbnb marketplace in its spatial constitution, as a network space brokering accommodation at specific places within designated city territories. It asks who dominates the digital marketplace across cities and time, distinguishing between professional and amateur listings. Based on an extensive dataset of 45 cities all over the world over a period of eight years, the paper investigates the distribution of amateur and professional listings. The article then focuses on the spatial diffusion of Airbnb listings in four selected cities (Amsterdam, Berlin, London, San Francisco) which represent diverse regulatory approaches, to identify local hotspots and establish who dominates these hotspots. The results show a worldwide trend of professional listings rising to dominate Airbnb, alongside few pockets of amateur marketplaces. Within cities, amateurs prevail only in local hotspots in specific cities—which, moreover, tend to be found only in peripheral locations. The results provide rich empirical insights into the commercialization and diversity of Airbnb as a network space around the world.
CRIS-Team Scopus Importer:2025-04-09
Keywords: Airbnb; Digital platforms; Sociology of markets; Sociology of space